2016
DOI: 10.1590/2317-1782/20162015099
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do tratamento fonoaudiológico após a laserterapia de baixa intensidade em pacientes com DTM: estudo descritivo

Abstract: RESUMO O aumento da dor/desconforto durante atividades como mastigar, falar e deglutir é comumente relatado por pacientes com Disfunção Temporomandibular (DTM) e a terapia fonoaudiológica miofuncional orofacial (TMO) tem sido proposta como parte do tratamento desta condição. Porém é uma modalidade que deve ser instituída quando o quadro de DTM e dor não está exacerbado a fim de não impedir ou dificultar a realização dos exercícios. Objetivo O objetivo deste estudo foi analisar o efeito da TMO no tratamento de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 15 publications
0
17
0
15
Order By: Relevance
“…However, despite not specifying the TMD subtype, this study demonstrated that physiotherapy approaches, whether performed by the individual alone or in conjunction with a Research, Society andDevelopment, v. 9, n. 10, e1729108485, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8485 professional manual approach, achieved, in a period of 4 weeks, effects in reducing pain and improving function . Another study, in which manual therapy was performed after analgesia with low-level laser therapy, showed a balance in the orofacial functions of the studied sample and a reduction in the remaining TMD signs and symptoms, according to the improved function, visual analog scale (VAS) and the self-assessment of the treated individuals (Melchior, et al, 2016).…”
Section: Exclusion Criteriamentioning
confidence: 87%
“…However, despite not specifying the TMD subtype, this study demonstrated that physiotherapy approaches, whether performed by the individual alone or in conjunction with a Research, Society andDevelopment, v. 9, n. 10, e1729108485, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8485 professional manual approach, achieved, in a period of 4 weeks, effects in reducing pain and improving function . Another study, in which manual therapy was performed after analgesia with low-level laser therapy, showed a balance in the orofacial functions of the studied sample and a reduction in the remaining TMD signs and symptoms, according to the improved function, visual analog scale (VAS) and the self-assessment of the treated individuals (Melchior, et al, 2016).…”
Section: Exclusion Criteriamentioning
confidence: 87%
“…Regarding the content evaluation, the MBGR Protocol includes the analysis of the orofacial structures and habitual posture of lips and tongue that may be altered in cases of TMD (16,19,24) ; mobility of the lips and mandible that may be impaired in this population (14)(15)(16)19) ; masticatory function, for which there is consensus among studies of the presence of disorder in this function (5,(14)(15)(16)(17)(18)(19)(20)(21)26) ; deglutition, referred to as atypical or adapted in cases of TMD (14,16,(19)(20)(21)(22)25) ; speech, allowing identification of cases with phonetic and TMJ disorders (14) . Thus, the MBGR Protocol encompasses the Orofacial Myofunctional Disorders (OMD) described in the literature for individuals with TMD.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen studies were selected after a literature review on functional changes presented by patients with TMD (5,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) according to the inclusion and exclusion criteria adopted (Chart 1).…”
Section: Mbgr Protocol -Content Validationmentioning
confidence: 99%
“…De acordo com os resultados apresentados, é possível observar uma diminuição dos sintomas dolorosos nos militares na condição de laser ativo. Isso vai de encontro a outros estudos na literatura que também demonstraram a recuperação dos pacientes quando se utiliza o laser de baixa potência [17,34,35].…”
Section: Discussionunclassified
“…Salienta-se que ao comparar o consumo de medicamentos à laser terapia como forma de abordagem terapêutica para o manejo da disfunção temporomandibular, nota-se que o consumo de medicamentos pode causar efeitos colaterais aos indivíduos a ele submetidos [16][17][18].…”
Section: Introductionunclassified